Gastroschisis and Omphalocele: A Case report - Kayastha, P; Paudel, S; Ghimire, RK; Ansari, MA (Nepalese Journal of Radiology, 2012)
Fetal gastroschisis and omphalocele are congenital defects of abdominal wall that are often diagnosed by prenatal ultrasound done for routine screening or for obstetric indications such as evaluating an elevated maternal serum alpha fetoprotein (AFP). Prenatal ultrasound could potentially identify the overwhelming majority of abdominal wall defects and accurately distinguish omphalocele from gastroschisis. Here we report two cases of gastroschisis and omphalocele diagnosed at routine prenatal ultrasound. NJR I VOL 2 I ISSUE 1 42-45 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6980